Ghana planning and implementation progress report for the CGIAR Initiative on Sustainable Intensification of Mixed Farming Systems - Odhong, Jonathan; Mponela, Powell; Kyerematen, R.; Abdul Rahman, Nurudeen (International Institute of Tropical Agriculture, 2022)
This report captures key outputs, and follow-up actions since the Ghana Country Planning and Inception Meeting for the Sustainable Intensification of Mixed farming Systems Initiative was held in Accra, Ghana, on 12 July 2022. Various partners have been engaged in the Initiative in Ghana so far, including the National Agricultural Research and Extension Systems (NARES), Universities, and National governments/ agricultural administrations (See participants list in Annex).